Sustainable Mobility and Lifestyle - La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2011)
“If you think green you move green”. This could be the slogan to summarize the goal this article try to affirm. Green mobility should be a new way of thinking and living tending to state a new culture of moving. Making people aware of environmental and social impacts of unsustainable travel choise and educating people are the key of success for any sustanable policy. Starting from this consideration this article selects and examimes some reports and documents that are particularly significant in research for greener ways of living. As shown in Ifort report on Usance of italian in mobility, car trips are always predominant over other ways of moving even though an inclination towards the change in using the car has been pointed out. Transport is the fastest growing sector in term of energy use and it is also the sector producing about 300 million tonnes of CO2 per year in the cities. The european commitment to achive at least a 20% reduction in greenhouse gas emissions in 2020 calls to do something about this situation. Somethings is happening at least at social level. People seem to be more conscious and disposable to modify own lifestyle, at same time is hard to please and less patient toward timimg of governmental procedures. This is “the social capital” able to govern the changement towards more livable cities. The experience of transition towns for example shows a “bottom down” solution based on engagement in changing actual development model strongly dependent on oil. The experiment involves about seven hundred cities around the world and is also expanding in Italy. It is a cultural movement that involves the community in accordance with local government. In the transition town model, collective action plays both a significant and active role in identifying the possibility to address the environmental emergency that involves all the existing cities. Other examples discussed in this article refer to “bottom up” solutions to tackle climate change in which the transport sector bears a heavy responsibility. These reports have all the same target - the urgency to respond to global climate change in urban centers- but different methodology to test how and how much is the commitment of govern and people to meet this challenge. What stands out is the awareness that current lifestyles must necessarily change in order to assure vivibility to the future generations. This article attempts to stimulate the attention of the scientific field about the possibilities that an in-depth study dealing with signals of changement may have.